The Lived Experiences of Teachers with Visual Impairments in the Inclusion of Students with Visual Impairments: A Phenomenological Study - Ayşe Dilşad Yakut; Hatice Şengül Erdem (Sakarya University Journal of Education)
This study aims to reveal the lived experiences of teachers with visual impairments (VI) in the inclusion of students with VI. In this phenomenological study, data were collected from 8 teachers with VI through semi-structured interviews and analyzed by content analysis using a qualitative software program named MAXQDA20. The six themes identified from the content analysis were underlying issues in inclusion, personal guidance of teachers on students with VI, critical evaluation of inclusion, from diagnosis to the IEP implementation, the appropriate model of education for students with VI, and teachers' sense of inclusion. The findings revealed that teachers with VI contributed to the inclusion of students with VI. Furthermore, they emphasized system-related issues preventing inclusive practices and made critical evaluations concerning practices in inclusive settings. Based on the findings, inclusive classrooms and resource rooms should be equipped with educational tools (i.e., the braille alphabet, assistive technologies, tactile graphs and maps), teaching staff and their training should be enhanced, and school buildings should be designed as physically accessible and supervised by special education teachers who have expertise in VI or experience in working with students with VI.